Diagnostic imaging modalities and surgical anatomy of the temporomandibular joint in rabbits. (February 2018) - Kyllar, Michal; Putnová, Barbora; Jekl, Vladimír; Stehlík, Ladislav; Buchtová, Marcela; Štembírek, Jan
The temporomandibular joint (TMJ) is a condylar synovial joint that, together with the masticatory muscles, controls mandibular movement during mastication. The rabbit is often used as a model species for studying the mechanisms of TMJ diseases, and in regenerative research. However, there are significant differences between rabbit and human TMJs that should be taken into account before using this model for experimental research. Here, we use several analytical approaches (radiography, computed tomography and magnetic resonance imaging) to enable a detailed description and analysis of the rabbit TMJ morphology. Moreover, possible surgical approaches have been introduced with a focus on available access into the rabbit TMJ cavity, which relate our findings to clinical usage.